BOTH MEDICAL AND SURGICAL TREATMENT FOR UNILATERAL PRIMARY ALDOSTERONISM LEAD TO BLOOD PRESSURE IMPROVEMENTS. (April 2021) - Puar, Troy; Kek, Peng; Ming, Lih; Loh, Wann; Lim, Dawn; Tin, Pei; Zhang, Meifen; Lee, Lynette; Swee, Du; Tay, Donovan; Tan, Saran; Khoo, Joan; et al.
Abstract : Objective: All patients with primary aldosteronism (PA) can be treated with medications but those with unilateral PA can be offered surgery (adrenalectomy). Since most patients confirmed to have unilateral PA by adrenal vein sampling undergo surgery, there is a paucity of data comparing the effects of medical versus surgical treatment in patients with unilateral PA. We applied a clinical prediction score to include patients with likely unilateral PA and assessed post-treatment blood pressure (BP) outcomes. Figure. No caption available. Design and method: 214 patients diagnosed with PA managed in two major tertiary centres in Singapore from 2000 – 2019 were identified for this retrospective analysis. Patients with confirmed unilateral PA by adrenal vein sampling were included. Patients with indeterminate subtype were categorised using our previously validated clinical prediction score, Aldosterone-potassium ratio (APR), and patients with APR > 10 (highly predictive of unilateral disease) were included. Results: Of 214 patients, 38 patients had confirmed unilateral PA on adrenal vein sampling, and another 78 patients had likely unilateral PA using APR score. Hence, 116 patients were included for analysis, median age 53 (46 – 60) yrs, 47 females (40.5%). 56 patients (48.3%) underwent adrenalectomy, and 60 patients (51.7%) were treated with medications (spironolactone, eplerenone or amiloride). In the surgical group, there was improvement in systolic and diastolic BP from 150 to 131 mmHg, P < 0.001 and 87 to 76 mmHg, P < 0.001 respectively, over a follow-up duration of 6.5 (3 – 9.25) yr. In the medical group, there was significant improvement in systolic and diastolic BP from 148 to 134 mmHg, P < 0.001 and 85 to 76 mmHg, P < 0.001 respectively, over a follow-up duration of 5 (2 – 11) yrs. In addition, post-surgery, there was a decrease in WHO-daily defined dose of antihypertensive medications from 1.8 to 0.8, P < 0.001, whereas it did not change in the medical group, from 2.2 to 2.0 medications, P = 0.337. Conclusions: Both medical and surgical treatment for unilateral primary aldosteronism led to significant blood pressure improvements. However, surgical treatment reduces the pill burden of hypertension medications, and offers the possibility of complete cure of hypertension.